Knowledge and awareness of bell’s palsy among undergraduate nursing students in Universiti Sains Malaysia - Jamaludin, Nurul Nabila (Universiti Sains Malaysia, 2024)
Bell's palsy (BP) is an unexplained episode of facial muscle weakness or paralysis (Johns Hopkins Medicine, 2023). It is a common neurological disorder that can have a significant impact on an individual's quality of life. This study aimed to determine the level of knowledge and awareness of Bell’s Palsy and its association among undergraduate nursing students at USM. Data were collected using a self-administered questionnaire. This research study included 127 undergraduate nursing students from the School of Health Sciences. The study was conducted using a convenience sampling method. Data collected were statistically analysed using the SPSS software version 27. The tests used in this study were descriptive statistics and Pearson Chi-square. The results show that more than half of the respondents presented with poor levels of knowledge regarding Bell’s Palsy, n=81 (63.8%). The majority of the respondents had also poor awareness of Bell’s Palsy (80.3%). Furthermore, the results of this study revealed that there is a significant association between knowledge and awareness of Bell’s Palsy, as indicated by the low P-value (<0.001). In conclusion, the low level of knowledge and awareness of Bell's Palsy among undergraduate nursing students is a serious issue that needs to be addressed. This gap can lead to delayed diagnosis, misdiagnosis, and inadequate management, resulting in poor health outcomes. Therefore, targeted educational initiatives and awareness campaigns are essential to improve awareness and knowledge of Bell's Palsy, ultimately enhancing patient care.